Entre o Mediterrâneo e o Atlântico, uma aventura teatral - Pupo, Maria Lúcia de Souza Barros (Comunicação & Educação, 1999)
This is a reflection on the work carried out by the author as the coordinator of a research-action using game and theatre practice workshops, with Moroccan university students, in the city of Tetuán. The work aims at demonstrating the convenience of experimentation and the evaluation of theatre practices that articulate games and narrative texts, and how they result positively in educating both students and teachers. The research-action considered the Arab World's cultural environment and searched for the articulation of theatre practices and games with the cultural tradition of the proverbs, leading groups of students to appropriate themselves of the text and to establish significant relations with it and from it. The result showed the convenience of theatre language to educate students, but also it demonstrated how theatre language is important for cultural respect and exchange.